Synthesis of Porous Carbons and Their Applications in Gas Uptake - Madkhali, Asma (2023)
The need to mitigate the negative environmental impacts of fossil fuel usage and the growing scarcity of these fuels have motivated the exploration and implementation of alternative approaches for carbon dioxide reduction and energy storage. Porous materials have been identified as a viable solution among the various strategies available. Porous carbons have exhibited considerable potential for numerous applications in this domain. The present dissertation conducts an investigation into porous carbons, with a particular emphasis on different synthesis methods and material characterisation. Additionally, the study examines the potential of these materials in terms of energy storage and gas adsorption applications.